Effectiveness of Public Services in the Two-Wheeled Motor Vehicle Tax Amnesty Program at the Samsat in Cirebon Regency - Diva Dwi Azahra; Yanto Heryanto (Athena: Journal of Social, Culture and Society, 2026)
This study examines the quality of public services in the implementation of the Motor Vehicle Tax Amnesty Program at the Cirebon Regency Samsat. Using a descriptive qualitative method and collecting data through in-depth interviews with the head of the Samsat, front office service officers, and taxpayers who directly benefited from the program. The research analysis framework refers to Campbell's effectiveness theory, which covers five main dimensions: program success, target success, level of satisfaction with the program, the relationship between input and output, and overall goal achievement. The results show that the amnesty program was able to encourage public participation by serving around 8,500–9,000 taxpayers and generating additional regional revenue of approximately Rp 45–55 billion. However, the effectiveness of the program is still influenced by a number of constraints, such as limited infrastructure, relatively long waiting times, and suboptimal human resource capacity. In general, this study concludes that the tax amnesty program is quite effective in increasing tax compliance and regional revenue, but it still requires strengthening of facilities and development of human resources in order to maximize its effectiveness.